Enhancing Competitive Advantage through Diversity Management: HR Strategies and Interventions. - Agrawal, Shuchi (Gyan Management Journal, 2008)
Today diversity in workplace has gain d immen e importance. A large number of large number of compani s are now linking workpla diversity to their strategic goal and objectives in order to remain comp titive in the face of changing demographics and the rapid globalization of business. By understanding and using diversity in innovative ways and developing proactiv approaches, organizations are encouraging the contributions of the diverse workforce .The challenge lie how best to do this. This paper tri s to consider how Diversity in workforce can be best managed so that it acts as a vital strategic resource for the organization .It also considers how HR practices can contribute to maximize the benefit of diverse workforce to give the organization 'that' competitive edge in the market.
Keywords: Interventions; Diversity Management; workplace; demographics; organization